Invasive Candidiasis in Non-Hematological Patients - Mikulska, Malgorzata (Università Cattolica del Sacro Cuore, 2011)
Candida is one of the most frequent pathogens isolated in bloodstream infections, and is associated with significant morbidity and mortality. In addition to haematological patients, there are several other populations with a substantial risk of developing invasive candidiasis (IC). These include patients undergoing prolonged hospitalisation with the use of broad-spectrum antibiotics, those fitted with intravascular catheters, admitted to both adult and neonate intensive care units (ICU) or gastrointestinal surgery wards and subjects with solid tumours undergoing cytotoxic chemotherapy. As a general rule, every immunocompromised patient might be at risk of Candida infection, including, for example, diabetic patients. The epidemiology of species responsible for IC has been changing, both at local and worldwide level, shifting from C. albicans to non-albicans species, that can be intrinsically resistant to fluconazole (C. krusei and, to some extent, C. glabrata), difficult to eradicate because of biofilm production (C. parapsilosis) or than might acquire resistance to azole during therapy. Delaying the specific therapy has been shown to increase morbidity and mortality, but traditional microbiological diagnosis is poorly sensitive and slow. Thus, culture-based treatment may result in therapy started too late. In order to reduce the mortality in IC, several management strategies have been developed: prophylaxis, empirical and pre-emptive therapy. Compared to prophylaxis, the latter approaches allow to reduce the use of antifungals by targeting only patients at very high risk of IC. Non-invasive serological markers and scores based on clinical prediction rules such as the presence of risk factors or Candida colonisation, have been developed with the aim of allowing prompt initiation of treatment. Although the use of these diagnostic tools in pre-emptive strategies is promising, the performance and cost-effectiveness should be tested in large trials. Agents recommended for initial treatment of candidemia in severely ill patients include echinocandins and lipid formulations of amphotericin B, while stable patients without risk factors for azole-resistance might be treated with fluconazole.